Apramycin and gentamicin resistance in Escherichia coli and salmonellas isolated from farm animals. - Wray, C. (Cambridge University Press, 1986)
Since the aminoglycoside antibiotic apramycin was licensed for veterinary use in 1980, all isolates of Escherichia coli and salmonellas received at the Central Veterinary Laboratory have been monitored for resistance to apramycin and the related antibiotic gentamicin. During the period 1982-4, the incidence of resistance in E. coli to apramycin increased from 0.6% in 1982 to 2.6% in 1984. In salmonellas the incidence of resistance to apramycin increased from 0.1% in 1982 to 1.4% in 1984. Resistance to both apramycin and gentamicin was detected in six different salmonella serotypes, although an isolate of Salmonella thompson from poultry was resistant to gentamicin but not apramycin. Most of the cultures were isolated from pigs, although the incidence of apramycin resistance in S. typhimurium (DT 204C) from calves has shown a recent dramatic increase. All the isolates with one exception produced the enzyme aminoglycoside 3-N-acetyltransferase IV (ACC(3)IV). The resistance was transferable by conjugation in most of the strains examined, and the plasmids specifying the resistance have been found to belong to a number of different incompatibility groups. Plasmids from three E. coli strains were compatible with all the reference plasmids and belonged to a previously undescribed group which was investigated further. It is suggested that bacteria from humans should be examined for resistance to apramycin and gentamicin to determine the possibility of the antibiotic-resistance bacteria, and their genes, spreading from animals to humans.